PERANAN KEPALA DUSUN DALAM MEMBANTU TUGAS KEPALA DESA DI KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Wardana, Data (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2016)
The article describing the result of research on the role of head of hamlet in assisting the head of the village in the Rambah Hilir District, Rokan Hulu Regecy. Where the background of this research is the lack of clarity of duties and rules on the role of the head of hamlet and to find out about the status and role should ideally be carried out by the head of hamlet in assisting the head of village. Other than that look at the factors that lead to less involvement of the head of hamlet in assisting the head of village.This is aqualitative research method of by linking research purposes with problems and symptoms that occur. Method of data collection is by interview, observation and documentation.Data were then collected and presented to the decision taken. The conclusions of this research, that the head of hamlet isrequired in the course of the village administrartion. The goal is to simplify the running of the village administration. Structurally the head of hamlet is as a territorial element, functionally role to assist the head of village duties.Although it is not spelled out any tasks that must be done, but the head of hamlet is able to perform the role by taking the initiative in helping the head of village.